PENGARUH PENDEKATAN PROBLEM CENTERED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X SMA NEGERI KABUPATEN SOLOK - Yusri, Radhya (JURNAL LEMMA, 2017)
This research was aimed at finding out (1) mathematic concept comprehention skills and mathematic problem solving skills, (2) mathematic concept comprehention skills and mathematic problem solving skills of students based on high and low knowledge, and (3) the interaction between of problem centered learning with the grade of primary ability in influencing the mathematic concept comprehention skills and mathematic problem solving skills. This research is a quasi-experimental research. Sample of this research is students at X Sains 2 SMAN 1 Lembah Gumanti and students at X Sains 1 SMAN 1 Hiliran Gumanti. The accumulation of data using test and the analysis of data by statistical. The results showed that (1) mathematic concept comprehension skills and mathematic problem solving skills of the students who were taught by using problem centered learning had high score than the students whose where taught by using conventional model 2) mathematic concept comprehension skills and mathematic problem solving skills of the students whose high primary ability that were taught by using problem centered learning had same score with the students who were taught by using conventional model 3) mathematic concept comprehension skills and mathematic problem solving skills of the students whose low primary ability that were taught by using problem centered learning had high score than the students who were taught by using conventional model 4)  whose were no interaction among the use of problem centered learning and the grade of primary ability in influencing the mathematic concept comprehention skills and mathematic problem solving skills.